Between fear and courage: Attitudes, beliefs, and behavior of liver transplantation recipients and waiting list candidates during the COVID‐19 pandemic. Issue 11 (27th June 2020) - Reuken, Philipp A.; Rauchfuss, Falk; Albers, Stefanie; Settmacher, Utz; Trautwein, Christian; Bruns, Tony; Stallmach, Andreas
Abstract : Patients with chronic liver disease and patients after solid organ transplantation (SOT) are vulnerable to severe coronavirus disease 2019 (COVID‐19). We evaluated fears, attitudes, and opinions associated with COVID‐19 in 365 SOT recipients (95% liver, 5% pancreas/kidney), 112 SOT candidates, and 394 immediate household contacts in 2 German transplant centers. Seven (1.5%) patients and 10 (2.5%) controls had contact with confirmed COVID‐19 cases. Fear of infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) was expressed by 65% of SOT recipients and by 55% of SOT candidates. SOT recipients had higher levels of fear of infection and more often wore personal protective gear than household controls. Female sex, steroid treatment, and using the local newspaper as a primary source of information were independently associated with expressed fear of infection in SOT recipients. Younger age and more recent transplantation correlated with concerns about severe COVID‐19 expressed by patients and with concerns about worse medical care expressed by household controls. One third of the patients expressed fear that immunosuppression could worsen COVID‐19 but only 15% used the transplantation center as a source of information. These data show that fears associated with the SARS‐CoV‐2 pandemic are frequently expressed but measures to prevent infection are regularly followed by patients before and after SOT. Abstract : Post–liver transplant patients often fear COVID‐19 and view hospitals as places of potential infection, although the majority follow preventive measures and take immunosuppressants.